PEDAGOGICAL AND METHODOLOGICAL CONDITIONS FOR DEVELOPING NATURAL SCIENCE LITERACY IN PHYSICS EDUCATION (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article examines the pedagogical and methodological conditions for developing natural science literacy in physics education within the context of modern teacher training. Natural science literacy is considered not only as the acquisition of theoretical knowledge, but also as the ability to explain physical phenomena, apply scientific concepts in real-life situations, interpret experimental data, and make evidence-based conclusions. The study emphasizes that physics education should be organized through problem-based learning, experimental activities, interdisciplinary integration, digital technologies, and competency-oriented assessment. Particular attention is given to the role of the teacher in creating a learning environment that develops students’ analytical thinking, scientific reasoning, observation skills, and practical problem-solving abilities. The article also highlights the importance of connecting physics content with everyday life, environmental processes, technological development, and social needs. It is argued that the effective development of natural science literacy requires a systematic combination of didactic principles, methodological tools, laboratory practice, and reflective learning strategies. The findings may be useful for improving physics teaching methodology in pedagogical higher education institutions and for preparing future physics teachers to organize modern, practice-oriented and scientifically grounded lessons.